ChemInform Abstract: Azobisisobutyronitrile Initiated Aerobic Oxidative Transformation of Amines: Coupling of Primary Amines and Cyanation of Tertiary Amines. Issue 14 (20th March 2013) - Liu, Lianghui; Wang, Zikuan; Fu, Xuefeng; Yan, Chun‐Hua
Abstract Oxygen is the sole oxidant, air or peroxide are not feasible.